3, 5-T2 alters murine genes relevant for xenobiotic, steroid, and thyroid hormone metabolism. (May 2016) - Lietzow, Julika; Golchert, Janine; Homuth, Georg; Völker, Uwe; Jonas, Wenke; Köhrle, Josef
Abstract : The endogenous thyroid hormone (TH) metabolite 3, 5-diiodo-l-thyronine (3, 5-T2 ) acts as a metabolically active substance affecting whole-body energy metabolism and hepatic lipid handling in a desirable manner. Considering possible adverse effects regarding thyromimetic action of 3, 5-T2 treatment in rodents, the current literature remains largely controversial. To obtain further insights into molecular mechanisms and to identify novel target genes of 3, 5-T2 in liver, we performed a microarray-based liver tissue transcriptome analysis of male lean and diet-induced obese euthyroid mice treated for 4 weeks with a dose of 2.5 µg/g bw 3, 5-T2 . Our results revealed that 3, 5-T2 modulates the expression of genes encoding Phase I and Phase II enzymes as well as Phase III transporters, which play central roles in metabolism and detoxification of xenobiotics. Additionally, 3, 5-T2 changes the expression of TH responsive genes, suggesting a thyromimetic action of 3, 5-T2 in mouse liver. Interestingly, 3, 5-T2 in obese but not in lean mice influences the expression of genes relevant for cholesterol and steroid biosynthesis, suggesting a novel role of 3, 5-T2 in steroid metabolism of obese mice. We concluded that treatment with 3, 5-T2 in lean and diet-induced obese male mice alters the expression of genes encoding hepatic xenobiotic-metabolizing enzymes that play a substantial role in catabolism and inactivation of xenobiotics and TH and are also involved in hepatic steroid and lipid metabolism. The administration of this high dose of 3, 5-T2 might exert adverse hepatic effects. Accordingly, the conceivable use of 3, 5-T2 as pharmacological hypolipidemic agent should be considered with caution.